Responses in species diversity in the Hulunbuir grassland to phosphorus addition under nitrogen-limiting and non-limiting conditions - Wang, Zhihui; Chen, Li; Pan, Yuzhen; Zhao, Dan; Yang, Yunrui; Li, Xinyu; Wang, Hongyi (Frontiers in Plant Science, 2024)
The phenomenon of nitrogen deposition resulting in species loss in terrestrial ecosystems has been demonstrated in several experiments. Nitrogen (N) and phosphorus (P), as major nutrients required for plant growth, exhibit ecological stoichiometric coupling in many ecosystems. The increased availability of nitrogen can exacerbate the ecological effects of phosphorus. To reveal the ecological effects of phosphorus under nitrogen-limiting and non-limiting conditions, we conducted a controlled N-P interaction experiment over 5 years in the Hulunbuir meadow steppe, where two nitrogen addition levels were implemented: 0 g N•m -2 •a -1 (nitrogen-limiting condition) and 10 g N•m -2 •a -1 (nitrogen-non-limiting condition), together with six levels of phosphorus addition (0, 2, 4, 6, 8, and 10 g P•m -2 •a -1 ). The results showed that nitrogen addition (under nitrogen-non-limiting conditions) significantly decreased species diversity in the steppe community, which was exacerbated under phosphorus addition. Under nitrogen-limiting conditions, phosphorus addition had no marked impact on species diversity compared to the control; however, there were substantial differences between different levels of phosphorus addition, exhibiting a unimodal change. Under both experimental nitrogen conditions, the addition of 6 g P•m -2 •a -1 was the threshold for affecting the community species diversity. Nitrogen addition reduced the relative biomass of legumes, bunch grasses, and forbs, but substantially increased the relative biomass of rhizomatous grasses. In contrast, phosphorus addition only markedly affected the relative biomass of forbs and rhizomatous grasses, with the former showing a unimodal pattern of first increasing and then decreasing with increasing phosphorus addition level, and the latter exhibiting the opposite pattern. The different responses of rhizomatous grasses and other functional groups to nitrogen and phosphorus addition were observed to have a regulatory effect on the changes in grassland community structure. Phosphorus addition may increase the risk of nitrogen deposition-induced species loss. Both nitrogen and phosphorus addition lead to soil acidification and an increase in the dominance of the already-dominant species, and the consequent species loss in the forb functional group represents the main mechanism for the reduction in community species diversity.